2006
DOI: 10.1038/sj.ijo.0803308
|View full text |Cite
|
Sign up to set email alerts
|

High monetary costs of dietary patterns associated with lower body mass index: a population-based study

Abstract: Introduction: Food choice is strongly influenced through economic constraints. The monetary costs for foods, especially those foods associated with a lower risk of obesity, have considerably increased during the last years. The purpose of this study was to determine the cost differences between low and high adherence to two dietary patterns which have been inversely associated with body mass index (BMI) and obesity. Methods: The subjects were Spanish men (n ¼ 1547) and women (n ¼ 1615) aged 25-74 years who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
155
4
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(177 citation statements)
references
References 39 publications
15
155
4
3
Order By: Relevance
“…Children with higher total HEI scores had a more expensive diet, and those spending the most money on food consumed a healthier diet. This is in line with other studies showing that healthy diets cost more (16)(17)(18)(19)(20)(21)24) . The magnitude of the difference in cost between healthy and less-healthy diets might seem rather small (h0?34/4184 kJ (1000 kcal)), but it corresponds to approximately h1000/ year for a family of four.…”
Section: Discussionsupporting
confidence: 93%
“…Children with higher total HEI scores had a more expensive diet, and those spending the most money on food consumed a healthier diet. This is in line with other studies showing that healthy diets cost more (16)(17)(18)(19)(20)(21)24) . The magnitude of the difference in cost between healthy and less-healthy diets might seem rather small (h0?34/4184 kJ (1000 kcal)), but it corresponds to approximately h1000/ year for a family of four.…”
Section: Discussionsupporting
confidence: 93%
“…The present findings may imply that public health interventions aimed at decreasing the energy cost of healthy diets could have a potential to improve population health. Consistent with previous Spanish (3) and Japanese (4) studies, we found that the monetary cost of dietary energy was negatively associated with BMI in a group of lean and young Japanese women. Additionally, we also found for the first time a negative relationship with waist circumference.…”
Section: Discussionsupporting
confidence: 91%
“…As this procedure gives only an approximation of actual diet costs, the results of the present study should be interpreted with caution. We note, however, that a similar methodology has been used in all previous observational studies (1)(2)(3)(4)(10)(11)(12)17) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As this procedure gives only an approximation of actual diet costs, the results of the present study should be interpreted with caution. We note, however, that a similar methodology has been used in all previous observational studies [5][6][7][8][9][10] . , size of residential area (city with $1 million; city with ,1 million; town and village), living status (living with family; living alone; living with others), current smoking (yes; no), current alcohol drinking (yes; no), current dietary supplement use (yes; no), currently trying to lose weight (yes; no), rate of eating (very slow; relatively slow; medium; relatively fast; very fast) and energy intake (kcal day 21 , continuous).…”
Section: Discussionmentioning
confidence: 99%